1995
DOI: 10.1002/ajmg.1320600516
|View full text |Cite
|
Sign up to set email alerts
|

Increased chromosomal breakage in tourette syndrome predicts the possibility of variable multiple gene involvement in spectrum phenotypes: Preliminary findings and hypothesis

Abstract: Increased chromosomal breakage was found in 12 patients with DSM-IV Tourette syndrome (TS) as compared with 10 non-TS control individuals with respect to untreated, modified RPM1-, and BrdU treated lymphocyte cultures (P < 0.001 in each category). A hypothesis is proposed that a major TS gene is probably connected to genetic instability, and associated chromosomal marker sites may be indicative of the localization of secondary genes whose altered expression could be responsible for associated comorbid conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In 1995, our research group at the University of Pretoria reported a small set of CFSs that could reliably distinguish between Tourette and non-Tourette individuals [34], and in a subsequent publication in 1996 [35] we speculated whether associated (variably) expressed FS could underlie endophenotypes which would explain (a genetic basis for) comorbidity in NPDs. In an evo-devo view, in 1995, Gericke proposed that an 'anthropogenetic' view of behavioral alteration may assist with the elucidation of genetic changes underlying neurobehavioral variation [36].…”
Section: Early Observations Of Chromosomal Fragility Observations Con...mentioning
confidence: 99%
“…In 1995, our research group at the University of Pretoria reported a small set of CFSs that could reliably distinguish between Tourette and non-Tourette individuals [34], and in a subsequent publication in 1996 [35] we speculated whether associated (variably) expressed FS could underlie endophenotypes which would explain (a genetic basis for) comorbidity in NPDs. In an evo-devo view, in 1995, Gericke proposed that an 'anthropogenetic' view of behavioral alteration may assist with the elucidation of genetic changes underlying neurobehavioral variation [36].…”
Section: Early Observations Of Chromosomal Fragility Observations Con...mentioning
confidence: 99%
“…In 1995, our research group at the University of Pretoria reported a small set of CFS which could reliably distinguish between Tourette and non-Tourette individuals [34], and in a follow up publication in 1996 [35] we speculated whether associated (variably) expressed FS could underly endophenotypes which would explain (a genetic basis for) comorbidity in NPDs. This concept was considered to imply that genes influencing higher brain functions may be situated at or near highly recombigenic areas allowing enhanced duplication and recombination following chromosomal strand breakage.…”
Section: Early Observations Of Chromosomal Fragility Observations In ...mentioning
confidence: 99%
“…CFS-associated duplication and deletion altering AT tract length and DNA flexibility have been linked with variation in nucleosomal architecture (Cosgrove & Walberger, 2005). AT-rich repeats mediate recombination events in non-homologous chromosomes during meiosis (Jackson et al, 2003) and due to a modification of binding factor characteristics, CFS have been proposed to contribute to epigenetic sensitive phenotypes (Woynarowski, 2004), a phenomenon which has been suggested to include neurobehavioral effects (Garofalo et al,1993;Gericke et al, 1995, Gericke 1998Simonic & Gericke 1996;Simonic & Ott, 1996;Savelyeva et al, 2006).…”
Section: How It All Comes Together: a Flexible Networking "Interface mentioning
confidence: 99%